Gleichenia linearis (Burm.) C. B. Clarke Leaves Extract Potent as a Medicinal Plant Based on Its Phytochemical Profile and The Total Phenolic Content - Swandi, Monica Kharisma; Salmi, Salmi (BERKALA SAINSTEK, 2023)
Resam fern (Gleichenia linearis (Burm.) C.B. Clarke) is a terrestrial plant that is easy to grow and has been used for medicinal purposes as by the community empirically. This study aimed to explore the potential of Gleichenia linearis (Burm.) C.B. Clarke) as medicinal plants based on their phytochemical profiles and total phenol content of the extract. Gleichenia linearis (Burm.) C.B. Clarke leaves were extracted with aquadest and methanol as a solvent by maceration method. Phytochemical content was detected qualitatively and the total phenol content was determined using colorimetric method with Folin-Ciocalteu reagent. As the result, qualitative screening for secondary metabolic contents in Gleichenia linearis (Burm.) C.B. Clarke extract found that the aqueous extract contains alkaloids, phenols, flavonoids, tannins, triterpenoids and steroids, but the saponin and steroid were not detected. In the methanol extract, all secondary metabolites were detected except triterpenoids. The total phenol content of methanol extract was higher than that of aqueous extract with levels of 127,08 mg/g GAE and 42,32 mg/g GAE, respectively. Based on these findings, it can be concluded that the Gleichenia linearis (Burm.) C.B. Clarke leaf has the potential to be developed as a medicinal plant.